PENGARUH OLAHRAGA AEROBIK INTENSITAS MODERAT DI RUMAH SEBAGAI UPAYA PENGELOLAAN STRES DI MASA PANDEMI COVID - 19 PADA MAHASISWA FK UMSU - ASHIL MUHAMMAD ABDUL RASYID; GUSBAKTI RUSIP (LP2MTBM MAKARIOZ, 2021)
Health protocol in covid-19 pandemic had impacted the daily live of the society drastically, students are no exception.Students are constantly faced with stressors that could potentially manifest into mental health problem if it were toaccumulate without relaxation period. One of the stress coping strategy is to exercise routinely, but the options are limiteddue to the health protocols. The type of exercise that could decrease perceived stress level is moderate intensity aerobicexercise. 32 samples with moderate perceived stress level are allocated into two groups which are intervention group andcontrol group. The samples in intervention group were instructed to follow the intervention prescription of moderate intensityaerobic exercise at home for 4 weeks and monitored online, whereas the samples in control group were not doing anyexercise. Stress level of all samples were measured before and after the period of intervention using PSS-10 questionnaire.Mann Whitney test result shows significant realtion between moderate intensity aerobic exercise at home and the studentsstress level with P value = 0.002 (p<0.05). Spearman’s rho shows the relation between variables are significant, with strongand positive correlation with correlation coefficient = 0.564. The result of this study has shown that moderate intensityaerobic exercise at home could be an option as an attempt to cope with stress in time of covid-19 pandemy.